Legal Protection for Consumers Against the Circulation of Illegal Cosmetics in Online Stores (E-Commerce) Reviewed from RI Law Number 17 of 2023 Concerning Health - Situngkir, Andreas Henfri; Fauzan, Fauzan; Sidi, Redyanto (Asian Journal of Healthcare Analytics, 2023)
Cosmetics are one of the beauty products that are in great demand by women in Indonesia, many women are interested in trying new products to follow the trend. In addition, cosmetics have also become a staple of women and do not rule out the possibility of being used by men. Therefore, cosmetics are one of the products that are required to have a distribution permit so that in their use and circulation it has sufficient legality and is not dangerous for consumers. However, in the practice of buying and selling, there are still many cosmetics sellers who are not official or do not have a distribution IDZIN aka illegal which is marketed through online stores or e-commerce. So that it then raises many problems that result in losses felt by consumers, in this condition consumers need fair legal protection. The purpose of this study is to find out what kind of protection or legal umbrella is able to protect consumers from the circulation of illegal cosmetics and ensnare the perpetrators of the trafficking. This study uses a normative research method with a statutory approach (statue approach) and conceptual (conceptual approach). The data source used in this study is RI Law Number 17 of 2023 concerning Health and other research relevant to the research.